(untitled) - Rhodes, John (Boston, 2001)
Covering a variety of solutions, Videoconferencing for the Real World explores the advantages and disadvantages of desktop systems, set-top systems, rollabout systems, and room systems. In addition to compression, multipoint conferencing and video distribution systems, this book also addresses topics such as, pilot projects, the preparation of RFPs, service contracts, training, content creation, and convergence. The text also includes information on conducting an effective needs analysis and the developing of solutions that will adapt easily to future changes in organizational requirements.
Keywords: Videoconferencing,Business communication,Cầu truyền hình,Kinh doanh truyền thông; Technological innovations,Đổi mới công nghệ